The Effect of Mitomycin C on Induction of Shiga Toxin Production in Clinical STEC Isolates - Surangi H. Thilakarathna; Brendon Parsons; Linda Chui (Toxins, 2025)
Early determination of the Shiga toxin type of Shiga toxin-producing Escherichia coli (STEC) is crucial for guiding STEC-infected patients for proper and timely treatment and patient care. Most diagnostic microbiology laboratories rely on PCR assays to detect the presence of stx1 and/or stx2 and enzymatic immunoassays (EIA) to detect the presence of the Shiga toxins 1 and/or 2 in STEC-positive stool samples. Occasionally, the stool samples test positive for STEC by PCR assays but test negative for the presence of Shiga toxins. Insufficient toxin production under laboratory conditions is the main culprit of this discordance. To test whether EIA-based STEC detection could be improved, various clinical STEC strains were treated with mitomycin C, which is a commonly used inducer of Shiga toxin production. A dose-dependent increase in Shiga toxin production, in response to mitomycin C doses of up to 500 ng/mL, was observed without any bactericidal effects. Depending on the serotype, 5–50 times more Shiga toxin 2 was produced than Shiga toxin 1. Shiga toxin production was not induced by the mitomycin C treatment in certain STEC serotypes carrying the toxin subtypes stx1a, stx2a, 2b, 2f, or 2h. This diversity in toxin production indicates that other factors may determine toxin expression in certain STEC strains, which warrant further exploration.